2003
DOI: 10.1002/cne.10693
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the exclusion zone in dopaminergic amacrine cell mosaics

Abstract: A fundamental organizing feature of the retina is the presence of regularly spaced distributions of neurons, yet we have little knowledge of how this patterning emerges during development. Among these retinal mosaics, the spatial organization of the dopaminergic amacrine cells is unique: using nearest-neighbor and Vornoi domain analysis, we found that the dopaminergic amacrine cells were neither randomly distributed, nor did they achieve the regularity documented for other retinal cell types. Autocorrelation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 56 publications
7
91
0
Order By: Relevance
“…One distinguishing feature of the VGluT3 + amacrine cell and type 2 bipolar cell populations is that each undergoes abundant overproduction during development that is subsequently pared down through Bax-mediated apoptosis, producing a mosaic with little more regularity (if any) relative to a random distribution of cells. The same has been shown for dopaminergic amacrine cells, a cell type that does not evidence tangential dispersion during development (17), but rather undergoes substantial Bax-mediated cell death (22), transforming a random distribution of cells into one with a marginally more regular distribution (4). In contrast, cholinergic amacrine cells and horizontal cells do not use selective cell death as a mechanism to increase mosaic regularity during development while both disperse tangentially via Megf-mediated homotypic interactions in the process of establishing their regularity (6,23,24).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…One distinguishing feature of the VGluT3 + amacrine cell and type 2 bipolar cell populations is that each undergoes abundant overproduction during development that is subsequently pared down through Bax-mediated apoptosis, producing a mosaic with little more regularity (if any) relative to a random distribution of cells. The same has been shown for dopaminergic amacrine cells, a cell type that does not evidence tangential dispersion during development (17), but rather undergoes substantial Bax-mediated cell death (22), transforming a random distribution of cells into one with a marginally more regular distribution (4). In contrast, cholinergic amacrine cells and horizontal cells do not use selective cell death as a mechanism to increase mosaic regularity during development while both disperse tangentially via Megf-mediated homotypic interactions in the process of establishing their regularity (6,23,24).…”
Section: Discussionmentioning
confidence: 54%
“…Recently, however, the EGF-like transmembrane receptor Megf10, which is expressed in only two neuronal populations of the retina, has been shown to mediate recognition and repulsion between like-type cells (3). In another retinal neuronal population, the anti-and proapoptotic factors Bcl2 and Bax have been shown to modulate programmed cell death, a process that yields increased regularity of this mosaic (4,5). Aside from these examples, relatively little is known about the genetic determinants that coordinate these retinal cell biological processes.…”
mentioning
confidence: 99%
“…This orderly arrangement of neurons of the same type is thought to ensure an even sampling of the visual field. Previous studies have shown that lateral cell displacement plays an important role in the formation of retinal mosaics (Galli-Resta et al, 1997;Reese and Galli-Resta, 2002;Reese et al, 1995), but simulation experiments (Jeyarasasingam et al, 1998) and studies of retinal mosaics in death-suppressing transgenic mice (Raven et al, 2003) strongly suggested that cell death also participates in this process. The present study provides direct evidence of a death control mechanism contributing to regular cell spacing and density in a neural population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the densities of the ChAT-positive (starburst) and DAB1-positive (AII) cells were slightly decreased. Dopaminergic amacrine cells rely in part on cell death to sculpt their mosaic pattern 20 . We saw decreased TdTmediated dUTP nick end labelling (TUNEL)-positive cells in the developing Dscam 2/2 retina, but saw no change in the number of proliferating cells ( Supplementary Fig.…”
mentioning
confidence: 99%